2012
DOI: 10.1155/2012/249501
|View full text |Cite
|
Sign up to set email alerts
|

Global Breast Cancer: The Lessons to Bring Home

Abstract: Breast cancer is the most common cancer affecting women globally. This paper discusses the current progress in breast cancer in Western countries and focuses on important differences of this disease in low- and middle-income countries (LMCs). It introduces several arguments for applying caution before globalizing some of the US-adopted practices in the screening and management of the disease. Finally, it suggests that studies of breast cancer in LMCs might offer important insights for a more effective manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…This finding must be strongly considered in thinking about any future strategies directed to this disease and the "late" presentation problem in Bangladesh. It certainly reinforces arguments made about the inapplicability of screening strategies from high incidence-high-income countries to countries with low incidence like Bangladesh (Formenti et al, 2012). Finally, our data support the feasibility of using a motivational video and importantly navigation whereby a community health worker accompanies a woman with a suspected serious breast problem, to a specialty health care facility, can get women into care.…”
Section: Discussionsupporting
confidence: 82%
“…This finding must be strongly considered in thinking about any future strategies directed to this disease and the "late" presentation problem in Bangladesh. It certainly reinforces arguments made about the inapplicability of screening strategies from high incidence-high-income countries to countries with low incidence like Bangladesh (Formenti et al, 2012). Finally, our data support the feasibility of using a motivational video and importantly navigation whereby a community health worker accompanies a woman with a suspected serious breast problem, to a specialty health care facility, can get women into care.…”
Section: Discussionsupporting
confidence: 82%
“…Breast cancer is a molecularly heterogeneous disease and the most common cancer affecting women all worldwide [29] . A previous study demonstrated that autophagy regulation has different and even opposite effects in breast cancer, indicating the need for a selection strategy when aiming to modulate autophagy in cancer therapy [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Over-referral represents the central negative issue with mammographic breast screening putting a high financial pressure on healthcare systems [9,10] as well as has great undue psychological impact on the patients [11,12]. Moreover, there is the adverse effect of misdiagnosis of malignant lesions reported as benign (false negatives) [13].…”
Section: Introductionmentioning
confidence: 99%